High-resolution imaging follow-up of doubly imaged quasars. Issue 2 (24th February 2021) - Shajib, Anowar J; Molina, Eden; Agnello, Adriano; Williams, Peter R; Birrer, Simon; Treu, Tommaso; Fassnacht, Christopher D; Morishita, Takahiro; Abramson, Louis; Schechter, Paul L; Wisotzki, Lutz
ABSTRACT: We report upon 3 years of follow-up and confirmation of doubly imaged quasar lenses through imaging campaigns from 2016 to 2018 with the Near-Infrared Camera2 (NIRC2) on the W. M. Keck Observatory. A sample of 57 quasar lens candidates are imaged in adaptive-optics-assisted or seeing-limited K ′ -band observations. Out of these 57 candidates, 15 are confirmed as lenses. We form a sample of 20 lenses adding in a number of previously known lenses that were imaged with NIRC2 in 2013–14 as part of a pilot study. By modelling these 20 lenses, we obtain K ′ -band relative photometry and astrometry of the quasar images and the lens galaxy. We also provide the lens properties and predicted time delays to aid planning of follow-up observations necessary for various astrophysical applications, e.g. spectroscopic follow-up to obtain the deflector redshifts for the newly confirmed systems. We compare the departure of the observed flux ratios from the smooth-model predictions between doubly and quadruply imaged quasar systems. We find that the departure is consistent between these two types of lenses if the modelling uncertainty is comparable.